THE WOMEN REPRESENTATION IN DETERGENT PRODUCT PACKAGING DESIGNS - dinda aryani (Master Program in Linguistics, Diponegoro University, 2013)
Gender representation in media often portrays stereotypes such as women representations constructed by culture and society often portraying women’s code of conduct. Seeing the issue, the study aims to reveal women representation in detergent packaging designs and its ideology behind it. The data collection is in the form of visual images. Kress and van Leeuwen’s (2006) Social Semiotics theory on Reading Images is applied to reveal women representation. Meanwhile, ideology is investigated with Barthes’ signification order. The results show that the women are mostly represented to be feminine, tender, motherly, mature, independent, warm, loving, caring, beautiful, attractive, friendly, and happy. The ideology constructed is femininity ideology conveyed through several ways: mass media codes, fashion, color and non-verbal codes. (118)Representasi gender di media sering memotret sterotype seperti representasi wanita bentukan oleh budaya dan masyarakat yang sering menggambarkan etiket kaum wanita. Melihat isu ini, penelitian bertujuan untuk mengungkap representasi wanita di desain kemasan detergen dan ideologi di baliknya. Data dikumpulkan dalam bentuk gambar-gambar. Teori Semiotik Sosial tentang Membaca Gambar oleh Kress dan van Leeuwen (2006) digunakan untuk mengungkap representasi wanita. Sementara, ideologi dilacak dengan menggunakan teori ‘significance order ‘ oleh Barthes. Hasil penelitian menunjukkan bahwa wanita sebagian besar digambarkan sebagai kaum yang feminin, lembut, keibuan, dewasa, mandiri, hangat, penuh kasih, peduli, cantik, menarik, ramah, dan bahagia. Ideologi yang terbentuk adalah ideologi feminitas yang disasmpaikan lewat beberapa cara: sandi mass media, sandi warna dan non-verbal. (114)